2022
DOI: 10.1242/jeb.244659
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rate increases with acclimation temperature and is associated with mitochondrial function in some tissues of threespine stickleback

Abstract: The metabolic rate (ṀO2) of eurythermal fishes changes in response to temperature, yet it is unclear how changes in mitochondrial function contribute to changes in ṀO2. We hypothesized that ṀO2 would increase with acclimation temperature in the threespine stickleback (Gasterosteus aculeatus) in parallel with metabolic remodeling at the cellular level but that changes in metabolism in some tissues and organs, such as liver, would contribute more to changes in ṀO2 than others. Threespine stickleback were acclima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Heart and intestine are not commonly explored for their association to organismal SMR, but variation in cardiac performance explains variation in MMR [69,70]. Previous studies have found evidence that mitochondrial efficiency or cytochrome C oxidase enzyme activity in muscle and liver is correlated with variation in SMR in fish [12,14,71], yet these were not supported by our measures of mitochondrial density (CS activity). By contrast, there was a positive relationship between mitochondrial density in the heart and SMR in the high food treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Heart and intestine are not commonly explored for their association to organismal SMR, but variation in cardiac performance explains variation in MMR [69,70]. Previous studies have found evidence that mitochondrial efficiency or cytochrome C oxidase enzyme activity in muscle and liver is correlated with variation in SMR in fish [12,14,71], yet these were not supported by our measures of mitochondrial density (CS activity). By contrast, there was a positive relationship between mitochondrial density in the heart and SMR in the high food treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Changes in mitochondria number, structure, and function represent an important part of animal development, and it has been demonstrated that adaption occurs as a result of aging [7], increased exercise [4], change in dietary composition [9], exposure to environmental stressors and temperature changes [6]. Thermal changes in the ambient environment can induce mitochondrial metabolic adaptation, and it can occur via different mechanisms that could include the adaption of mitochondrial phosphorylation respiration rate, mitochondrial complex II/I activity, or cytochrome c oxidase activity [28]. For this study we only measured mitochondrial DNA quantity and used this as a proxy for mitochondria number.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating variation in mitochondrial metabolism provides an opportunity for integrating how mechanisms at the cellular level constrain whole-organism traits [6][7][8][9]. For example, individual variation in SMR and MMR were positively associated with proton leak respiration in hepatic mitochondria (i.e.…”
Section: Introductionmentioning
confidence: 99%